Staging the dark times: contemporary dystopian theatre in the UK 2000-2019 - De Simoni, Laura (2021)
This thesis explores contemporary manifestations of dystopian theatre. Through a detailed analysis of ten carefully selected plays and performances premiered in the UK from the year 2000 onwards, it aims to identify the key traits, mechanisms, and functions specific to the genre. Despite the proliferation of theatre with dystopian thematic concerns in the UK since the turn of the twenty-first century, with a few notable exceptions the critical scholarship on dystopia tends to concentrate on other forms, especially the novel, at the expense of the theatrical medium. My thesis aims to redress this imbalance. By bringing together concepts from Utopian Studies and critical approaches to drama and performance studies, I develop a specialist, innovative framework for the analysis of dystopian theatre.